Peran Biker Travelers sebagai Stakeholder dalam Mempromosikan Batur Unesco Global Geopark, Kintamani, Bali - Tyas, Wahyu Ning; Mahendra, Made Sudiana; Bhaskara, Gde Indra (Jurnal Master Pariwisata (JUMPA), 2020)
This study aims to determine the role of biker travelers in promoting Batur UNESCO Global Geopark, Kintamani, and to know their potition as a stakeholder. The research method used was descriptive qualitative. The technique of determining informants using purposive sampling. Data collected through observation, interviews, and documentation. The results show that Denpasar biker travelers have some roles in promoting Batur UNESCO Global Geopark through activities on their motorbike communities such as, touring, sunmori (sunday morning ride), planting trees in tourist areas, Bali no trash challenge activities, and using features on Instagram social media (hashtag (#), tag people, tag location and caption) to share photos and videos of their trip. Biker travelers are identified in the type of dormant stakeholder. The characteristics of this stakeholders are people or groups who have little or no interaction/involvement. It is recommended to the manager of Batur UNESCO Global Geopark to make an anual event that suits the biker travelers’ preferences, make an attractive brochure about tourism spot in Batur geopark , dare to invest in promotion, and optimize the synergy among stakeholders, particularly the Denpasar biker travelers in the development of the Batur UNESCO Global Geopark tourism promotion. Keywords : biker travelers, stakeholders, promotion